The growing Russophilia of post-communist Bulgarian nationalism: between entanglements and paradoxes: La creciente rusofilia del nacionalismo búlgaro poscomunista: entre enredos y paradojas - Stanchev, Evlogi (Araucaria, 2023)
The essay examines the various manifestations of Russian influence on present-day Bulgarian nationalism. Although this phenomenon dates back to the early days of Bulgarian nationalist thought in the 19th century, it gained particular prominence in recent years, especially in the context of Russian hybrid warfare. After outlining the political landscape of Bulgarian nationalism in the post-communist period, the article offers an in-depth analysis of the dominant pro-Russian narratives that are vociferously reproduced by the country’s major nationalist actors. While some of these messages have been firmly adapted in the collective memory of generations of Bulgarians due to various historical reasons (e.g., the narrative of the “Russian liberators”), others are a direct product of today’s Kremlin propaganda (the notions of the alleged “decadence” of the West). Furthermore, the growing divisions within Bulgarian society that took shape against the background of this prolonged Russian influence have also been thoroughly addressed. The paper argues that Kremlin-backed actors are trying to monopolize and privatize the patriotic discourse in Bulgaria, thereby disrupting the country’s pro-Western orientation.